التحليل الاقتصادي للمشكلة البيئية - خوري عصام; ناعسة عبير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
توضح هذه الدراسة عمق وأبعاد مشكلة التلوث البيئي التي باتت ظاهرة عالمية لها أبعادها الخطيرة. ولا تزال أدبيات اقتصاديات البيئة في طورها الأول, فقد استخدم الاقتصاديون الطرق الكمية للوصول إلى الامثلية التي توفق بين العلاقات التبادلية التي تكتنف الكثير من القضايا الاقتصادية البيئية, ومن بين تلك الطرق تحليل التكلفة-المنفعة. وبما أن مشكلة حسم العلاقة التبادلية بين التنمية والبيئة هي قضية عائدات (التنمية ) وتكاليف (للمشاكل البيئية المرتبطة بالتنمية) فإن تحليل التكلفة- العائد يعتبر من أهم وأفضل الطرق المعروفة حالياً للوصول إلى تلك الغاية بالرغم من بعض الصعوبات التي تعترض تطبيقه كصعوبة تحديد معدل الخصم الاجتماعي وإشكالية حساب التكاليف الاجتماعية (الخارجية). ولقد حاول البحث أيضاً عرض بعض الحلول للتلوث البيئي على اعتبار أنه مؤثر خارجي كاعتماد فرض ضرائب بيئية جديدة واستخدام طريقة الأسواق المفقودة... وصولاً إلى بعض النتائج والتوصيات التي تستهدف أهمية اعتماد التحليل الاقتصادي للمشكلة البيئية. This study sheds light on the depth and dimensions of the problem of environmental pollution, which turns to be a world phenomenon with serious consequences which are still at preliminary stage. Economists employ quantative methods seeking optimality that accommodates reciprocal relationships embodied in many of the environmental economic issues; one of those methods being the benefit-cost analysis. Given that the problem of determining the reciprocal relationship between development and environment is one of developmental output and costs of developmental environmentally-related problems, the process of benefit-cost analysis is the most significant, widely known method for attaining that goal, despite some difficulties facing application, like difficulty in defining social discount rate and that of calculating external social costs. Some have attempted to offer some solutions to environmental pollution by imposing new environmental taxes, using the method of (missing markets), and concluding with some results and recommendations geared to highlighting the importance of adopting economic analysis for handling environmental problems.